Microsoft System Center Configuration Manager Advanced Deployment : design, implement, and configure System Center Configuration Manager 2012 R2 with the help of real-world examples /: design, implement, and configure System Center Configuration Manager 2012 R2 with the help of real-world examples. (2014) - Coupland, Martyn
No abstract available